Levator ani defect status and lower urinary tract symptoms in women with pelvic organ prolapse - Morgan, Daniel M. (2009)
OBJECTIVES: Among women with pelvic organ prolapse, compare rates of lower urinary tract symptoms by levator ani defect (LAD) status. METHODS: Urinary incontinence and obstructive voiding are analyzed among 151 women with prolapse whose LAD status was determined with magnetic resonance imaging. RESULTS: Women with major LAD are less likely than women with normal muscles to experience stress incontinence when “coughing, laughing, or sneezing” (OR 0.27) and when “twisting, reaching, lifting, or bending over” (OR 0.26). They are less likely to have obstructive symptoms characterized by assuming an “unusual toileting position” or changing “positions…to start or complete urination” (OR 0.27). Women with minor LAD are more likely than those with normal muscles to experience stress incontinence with exercise (OR 3.1) and urge incontinence (OR 4.0). CONCLUSION: Lower urinary tract symptoms are less common among women with prolapse and major levator ani defects and more common among those with minor defects.